The relationship between the diffusion of innovation and E-Learning towards students development. - Hafizudien Mohd Nor; Lim Jia Yee; Nooryasmin Emalin Azhar; Nurul Ain Izzati Jusoh (2024)
The conventional or face-to-face teaching and learning process has changed to virtual or internet-based learning or electronic learning due to the presence of the COVID-19 epidemic. This study is to determine the relationship of diffusion of innovation and e-learning adoption among undergraduate students in higher education. This study was created to identify the level of innovation in the use of e-learning among undergraduate students in higher education. Specifically, it will investigate the relationships among relative advantage, compatibility, complexity and observability and information quality for students who are directly related to the following purpose. The analysis was conducted using quantitative research methods which were shared on the google form via link to collect data from 371 respondents in UMK. The UMK students will be the respondents because they are using the e-learning platform in their studies. According to the findings of this study, relative advantage, compatibility, complexity and observability and information quality all have a positive relationship with e-learning adoption. The study's findings will be useful to all students so that they are informed about the innovation of UMK students in using the application of e-capsule during their time in college. From the result, 35.6% of the respondents have used the e-capsule adoption to check the lecture schedule. Lastly, examining educators and institutional perspectives involves investigating how educators and educational institutions perceive and approach the integration of digital learning. This area of research explores the attitudes, beliefs, and experiences of educators regarding the adoption of e-capsule tools, as well as the broader institutional strategies and policies in place to support or hinder such adoption. By exploring educators and institutional perspectives, researchers can gain insights into the dynamics that shape the adoption and implementation of e-capsule.